Propuesta Pedagógica Etno-Ambiental para Mitigar la Deforestación (2021)
This research work is developed in the Chenche Balsillas Educational Institution of Coyaima Tolima specifically in students of the fifth grade of elementary school, this, focuses on mitigation processes for deforestation which was developed from a qualitative approach with different techniques and Instruments in the design and implementation taking into account the pedagogical realization in the identification of the problem to achieve evidence that specifically this problem that occurs in this community is deforestation, indicating that the Educational Institution is part of an indigenous community which is developing this research in marked to an Ethnoeductive approach in the intervention and development of strategies to implement the didactic proposal where they show us effective results during the implementation, so that in order to know the students' prior knowledge and knowledge, a PRE and POS as a way of evaluating previous concepts, and theoretical foundations.